2011
DOI: 10.17221/3283-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term organic amendments on chemical and microbial properties of a luvisol

Abstract: We studied the long-term effect (about 45 years) of farmyard manure, sewage sludge and compost application in two increments on organic carbon (C org ), the amount (C mic ) and activity of the microbial biomass (soil respiration, dehydrogenase activity), total N content and N delivery of soils as compared to manuring with mineral fertilizers. The application of both increments of compost and the high sewage sludge application rate resulted in an increase in C org while soils treated with both compost applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
34
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
11
34
1
Order By: Relevance
“…The NMS analysis showed different responses related to CTS amendment over the six years and suggested that there was an improvement in the chemical properties of the soil at the highest rate of CTS application. Previous studies with organic compost also found a strong improvement in soil fertility (Scherer, Metker, & Welp, 2011;Patel & Patra, 2014). In addition, the soil structure was better with the amendment of CTS at a high application rate, which indicates that high levels of CTS may improve the physical properties of soil in the long-term.…”
Section: Resultsmentioning
confidence: 69%
“…The NMS analysis showed different responses related to CTS amendment over the six years and suggested that there was an improvement in the chemical properties of the soil at the highest rate of CTS application. Previous studies with organic compost also found a strong improvement in soil fertility (Scherer, Metker, & Welp, 2011;Patel & Patra, 2014). In addition, the soil structure was better with the amendment of CTS at a high application rate, which indicates that high levels of CTS may improve the physical properties of soil in the long-term.…”
Section: Resultsmentioning
confidence: 69%
“…The long-term application of FYM, as a rule, increased the C org content of the soil (Dunjana et al, 2012;Fageria, 2012;Šimon, Czakό, 2014;Blanchet et al, 2016). However, as showed by Scherer et al (2011), after 45 years of repeated applications of FYM (every second year 4.5 and 9.0 t ha -1 on a dry weight basis) the C org content did not significantly differ from the control.…”
Section: Resultsmentioning
confidence: 86%
“…In addition, soil collected from the cultivation of maize in reduce tillage was characterized by a high biological activity. Soil microorganisms play a fundamental role in promoting growth and development of plants (Scherer et al 2011, Zhang et al 2012. The yield of maize (grain, straw) correlated with some biological activity of soil (Table 6).…”
mentioning
confidence: 99%